Prostate cancer high dose-rate brachytherapy: review of evidence and current perspectives. (2nd January 2018) - Dutta, Sunil W.; Alonso, Clayton E.; Libby, Bruce; Showalter, Timothy N.
ABSTRACT: Introduction : Patients with intermediate to high risk disease (prostate specific antigen (PSA) ≥ 10, Gleason score ≥ 7, or clinical stage ≥ T2b) suffer from poorer long-term biochemical control (freedom from an increasing prostate specific antigen level) when treated with external beam radiation (EBRT) alone. In order to improve biochemical control while limiting long-term complications, brachytherapy has been incorporated into radiotherapy treatment, either alone or in combination with EBRT. Areas covered : Current literature regarding the use of high dose-rate (HDR) brachytherapy for localized prostate cancer, including as a boost and monotherapy. The efficacy and toxicities of various approaches are evaluated including comparisons to low dose-rate (LDR) brachytherapy. Expert commentary : Prostate HDR brachytherapy has higher conformality than EBRT, potentially improving the therapeutic ratio by allowing higher doses per fraction to tumor cells. The improved biochemical control shown in trials have resulted in EBRT plus brachytherapy to be included as a standard treatment option supported by the NCCN and ASCO guidance documents for intermediate to high risk prostate cancer.